Environmental sound recognition in embedded systems: bridging experiments in passenger vehicles to autonomous vehicle applications in smart cities - Florentino, André Luiz (2024)
The autonomous vehicle market is experiencing significant growth, with indications of transitioning from the "trough of disillusionment" to the "slope of enlightenment" on the Gartner hype cycle chart. Fundamental technologies encompassing extensive data analytics, computational capabilities, and sensor fusion techniques have already been established, and all stakeholders in this industry are persistently exploring novel approaches to enhance the overall perception of end users in terms of safety and trustworthiness. In this context, this project aims to develop and implement an Environmental Sound Recognition (ESR) algorithm in an embedded system for deployment in autonomous vehicles for Smart Cities in 2025, targeting advanced functionalities for early warning systems. Due to hardware constraints, a regular passenger vehicle was used, embedding the ESR algorithm in a Raspberry Pi with a microphone array. The limited literature on ESR algorithms for vehicles primarily focuses on siren detection without real-time inferences, and to address this, a dataset benchmarking study confirmed classifiers’ accuracy, leading to the creation of a new dataset tailored to autonomous vehicles. This new dataset provided a comprehensive baseline where several classifiers were trained and evaluated for accuracy, memory usage, and prediction time, with CNN 2D using aggregated features emerging as the top-performing model, achieving an average accuracy of 80% in the sliding window process. During the indoor experiment, the total prediction time attained an average of 47.6 ms, validating the algorithm’s performance with weighted F1-scores close to or better than cross-validation results. In the final phase of the methodology, real-world tests conducted in a passenger vehicle yielded similar results. However, inconsistencies were observed in certain classes due to insufficient sample diversity and environmental noise, which affected their accuracy. The results of this project indicate that its general objective was successfully achieved, contributing to understanding of ESR algorithms in embedded systems within passenger vehicles, and it is ready for integration into the electric and electronic architecture of autonomous vehicles for Smart Cities. Additionally, upon conducting further experiments across various vehicle categories to assess cabin insulation effects, this project could potentially enhance safety features for drivers with hearing impairments by adapting the ESR algorithm as an add-on feature in regular passenger vehicles